Coccolithophore variability from the Shackleton Site (IODP Site U1385) through MIS 16-10 - MAIORANO, Patrizia; MARINO, Maria; Balestra, B.; Flores, J. A.; Hodell, D. A.; Rodrigues, T. (Global and Planetary Change, 2015)
Coccolithophore assemblages have been investigated at Integrated Ocean Drilling Program Site U1385, on the western Iberian margin, through Marine Isotope Stage (MIS) 16 to 10, between the end of the Mid-Pleistocene Transition and the Mid-Brunhes interval, with the aim to reconstruct orbital and millennial-scale surface water modifications. Assemblage variations are interpreted in terms of paleoclimate and paleoproductivity proxies. The pattern of C37 alkenones is also presented as an additional indicator of primary paleoproductivity. The overall proxies are compared with the available benthic and planktonic δ18O records and Ca/Ti profile. A newbenthic and planktonic δ13C dataset is also shown. The coccolithophore abundance mirrors the Ca/Ti pattern indicating that coccolith-derived carbonate is the dominant contributor to carbonate production in the studied interval. The distinct increase in the coccolithophore abundance, as well as in the accumulation rate, occurring at the MIS 14/13 transition, reflects the beginning of the worldwide-scale mid-Brunhes blooming of Gephyrocapsa caribbeanica and triggers the increase in carbonate production imprinted on the Ca/Ti profile. Interglacials are marked by enhanced abundances of the coccolithophore warm water group (wwt group) that also displays high frequency variability related to precessional/insolation forcing. Warmest surface water conditions are recorded during MIS 15, suggesting an intensified contribution of the subtropical AzC, essentially during MIS 15.5 and 15.1. Reduced productivity in these intervals is in agreement with a major influence of nutrient-poor and less ventilated subtropical waters. On the other hand, productive and mixed surface water conditions can be inferred during MIS 13 in agreement with other North Atlantic records. A long lasting period of warm, stratified and oligotrophic waters is inferred during MIS 11.3, indicating a continuous and more persistent influence of subtropical waters at the site location. Glacial phases are marked by ...